Pannexin-1 channels bridge apoptosis to NLRP3 inflammasome activation. (4th July 2019) - Demarco, Benjamin; Chen, Kaiwen W.; Broz, Petr
ABSTRACT: Apoptosis can promote inflammation by triggering activation of the NLRP3 inflammasome (NLR family, pyrin domain containing 3). However, the molecular mechanisms regulating these processes are ill-defined. We recently reported that pannexin-1 is required to promote NLRP3 inflammasome assembly. We further demonstrate that differential cleavage of gasdermin D (GSDMD) by apoptotic caspases regulates inflammatory cell lysis. Here, we discuss our findings and perspectives for future studies.